Multivessel Coronary Artery Dissection in a Patient with Co-Occurrence of Aortic Dissection and Dilated Cardiomyopathy in the Postpartum Period - Takahiro Kurihara; Eisuke Amiya; Masaru Hatano; Junichi Ishida; Shun Minatsuki; Shunsuke Inoue; Seitaro Nomura; Hiroyuki Morita; Issei Komuro (Diseases, 2023)
The co-occurrence of dilated cardiomyopathy (DCM) and aortic dissection has been rarely reported. Here, we present the case of a patient with co-occurrence of DCM and aortic dissection, wherein multivessel coronary artery dissection eventually occurred, thereby leading to advanced heart failure. She suffered from co-occurrence of DCM and aortic dissection 6 years ago. After the heart failure had briefly stabilized, the myocardial infarction due to coronary artery dissection led to worsening mitral regurgitation and decreased right ventricular function, thereby worsening the status of her heart failure. In addition to cardiovascular abnormalities, the patient was also complicated by short stature (145 cm), mild scoliosis, nonfunctioning pituitary adenoma of 1 cm in size, and retinitis pigmentosa. Coronary artery dissection is a possible complication in patients with co-occurrence of DCM and aortopathy, which could dramatically affect the clinical course of advanced heart failure.